A method for preparing a silicon-oxygen composite material, its product and application in lithium-ion batteries
By covering metal elements and carbon layers on the SiOx surface, prelithiation and coating of silicone sources, a silicon oxygen composite material with excellent first-time Coulomb efficiency and high cycle stability was prepared, and traditional silicon oxygen materials were solved. Inadequate performance problems in lithium-ion batteries.
Patent Information
- Application Number
- CN202211151865.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-09-21
AI Technical Summary
The theoretical capacity of traditional graphite negative electrode materials is relatively low. When silicon is used as an negative electrode material, the volume expansion rate is high, the material is prone to breaking and falling off, and the battery is low for the first time and has poor cycle stability.
The raw materials of metal elements are uniformly coated on the SiOx surface by ball milling, and carbon coating is carried out to form a SiOx material with a carbon-containing coating layer with pores. Silicon is prepared by prelithiation reaction and coating of an organic silicon source Oxygen composite material.
The first Coulomb efficiency and cycling performance of the silicon oxygen negative electrode material are significantly improved, the residual amount of prelithiation reagent is reduced, and the problems of pH increase and volume expansion are avoided.
Smart Images

Figure CN115939334B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a method for preparing a silicon-oxygen composite material, a product thereof, and an application of the same in lithium-ion batteries. Background Art
[0002] In recent years, with the continuous development of new energy technologies, lithium-ion batteries have been widely used. However, the theoretical capacity of traditional graphite-based negative electrode materials is low and cannot meet the market demand for high energy density of lithium-ion batteries. Studies have shown that single silicon has a high theoretical capacity. However, in practice, it is found that when silicon is used as a negative electrode material, its volume expansion rate reaches 300%, the slurry particles are easy to break and fall off, and the battery's first coulombic efficiency is low and the cycle stability is poor. Silicon-oxygen materials have attracted widespread attention as high-specific capacity negative electrode materials, but the resulting low first efficiency and poor cyclability limit the widespread application of this material. Therefore, improving the first coulombic efficiency and cycle performance of silicon-oxygen negative electrode materials has become an urgent problem to be solved.
[0003] Based on this problem, many material researchers have proposed the idea of pre-supplementing lithium after continuous attempts, that is, doping some metallic lithium while synthesizing the negative electrode material to compensate for the irreversible lithium element consumed in the battery reaction and improve the battery's first coulombic efficiency. The first coulombic efficiency of silicon oxide materials can be significantly improved by pre-lithiation, but pre-lithiated silicon oxide materials often encounter some problems in the process of preparing battery poles, such as increased pH value when preparing aqueous slurry, easy gas production, easy generation of particles and pores when slurry is coated, etc., resulting in poor electronic conductivity of lithium-containing silicon oxide materials, low first coulombic efficiency and cycle performance. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention discloses a method for preparing a silicon-oxygen composite material, which can effectively improve the efficiency of the pre-lithiation reaction and reduce the residual amount of the pre-lithiation reagent, thereby avoiding the increase in pH value when used as a negative electrode material, resulting in high residual alkali content and gas production during processing; and effectively alleviates the volume expansion of the silicon-oxygen material. The prepared silicon-oxygen composite material has excellent first coulomb efficiency, first reversible capacity and cycle stability.
[0005] The specific technical solutions are as follows:
[0006] A method for preparing a silicon-oxygen composite material comprises the following steps:
[0007] (1) SiO x Ball milling with raw materials containing metal elements to obtain SiO x ; The SiO x x is selected from 0.8 to 1.5;
[0008] The raw material containing metal elements is selected from metals and / or oxides of metal elements, and the metal elements are selected from one or more of the metal elements of the first main group to the fourth main group, and the metal elements of the first sub-group to the seventh sub-group;
[0009] SiO x The mass ratio of the raw material containing the metal element is 100:1 to 50;
[0010] (2) SiO2 prepared in step (1) with a surface layer containing metal elements x Carbon coating treatment is performed to obtain SiO x Material;
[0011] (3) The SiO2 containing carbon coating prepared in step (2) x The material was immersed in an acidic solution and then separated after acid washing to obtain a porous carbon-containing coating layer of SiO x Material;
[0012] (4) The SiO2 having a porous carbon-containing coating layer prepared in step (3) is x The material is mixed with a pre-lithiation agent and calcined to obtain pre-lithiation SiO x ;
[0013] (5) using an organic silicon source to treat the pre-lithiated SiO prepared in step (4) x The silicon-oxygen composite material is obtained by coating and then post-processing.
[0014] The present invention discloses a method for preparing a silicon-oxygen composite material. Firstly, a raw material containing metal elements is uniformly coated on SiO by ball milling. x The surface is then carbon coated to obtain a SiO x Materials; then pickling treatment to remove SiO x The metal layer coated on the surface is removed, and a pore structure is formed on the coated carbon layer. This pore structure not only improves the efficiency of the pre-lithiation reaction and makes the pre-lithiation reagent basically free of residue in the subsequent pre-lithiation process, but also alleviates the volume expansion of the material in the pre-lithiation process; finally, a silicon-oxygen composite material is prepared after a step of coating with an organic silicon source. This preparation method adopts first coating the metal / metal oxide layer, then removing it by acid washing, and coordinating with the last step of coating with an organic silicon source. It not only solves the high alkalinity caused by the residual pre-lithiation reagent in the traditional process, but also further solves the problem of easy gas generation when preparing the aqueous slurry, and easy generation of particles and pores when the slurry is coated; and effectively alleviates the volume expansion of the silicon-oxygen material.
[0015] It was found through experiments that SiO x The mass ratio of SiO to raw materials containing metal elements is particularly important. xThe mass ratio of the raw material containing metal elements is controlled at 100:1-50, and the pH value of the prepared silicon-oxygen composite material can be controlled below 10, specifically 7-10, preferably 7-9.8, with the coating of the organic silicon source in the last step; and no gas generation occurs. The experiment further found that with the increase of the amount of raw materials containing metal elements, the pre-lithiation SiO x The residual pre-lithiation reagent in the pre-lithiation agent further reduces the pH value of the prepared silicon-oxygen composite material. However, the experiment also found that when the amount of raw materials containing metal elements is too large, the subsequent coated carbon layer will collapse significantly after acid washing. Preferably, SiO x The mass ratio of the silicon-oxygen composite material to the raw material containing metal elements is 100:1 to 10. The lithium-ion battery assembled from the silicon-oxygen composite material prepared under the above further preferred range has excellent first coulombic efficiency, first reversible capacity and high cycle stability.
[0016] More preferably, the ratio is 100:1 to 6, and more preferably 100:6. As the mass ratio of the two is continuously optimized, the electrochemical performance of the lithium-ion battery assembled from the prepared silicon-oxygen composite material is further optimized.
[0017] The experiment also found that if the organic silicon source is not coated or is coated with an ordinary carbon layer, or even if it is coated with a hydrophobic long-chain alkyl, such as lauric acid, gas production will occur, thereby affecting the final electrochemical performance.
[0018] In step (1):
[0019] The SiO x The median particle size of the raw material containing metal elements is 2.0 to 8.0 μm, the median particle size of the raw material containing metal elements is 0.01 to 5.0 μm, and SiO x The median particle size of the raw material is larger than the median particle size of the raw material containing the metal element;
[0020] Preferably, the SiO x , x is selected from 0.8 to 1.0, and more preferably x=1.0.
[0021] Preferred:
[0022] The metal element is selected from one or more of the metal elements of the first main group to the fourth main group, and the metal elements of the first sub-group to the fourth sub-group;
[0023] More preferably, the metal element is selected from one or more of Cu, Na, Mg, Al, Sn, Zn, and Ti. Even more preferably, the metal element is selected from one or more of Cu, Mg, and Zn.
[0024] The ball milling includes dry milling or wet milling. If wet milling is used, conventional solvents in the art, such as one or more of anhydrous ethanol, ethylene glycol, and acetone, are used.
[0025] The ball mill uses grinding balls with a diameter less than 20 mm, such as one or more grinding balls with a diameter of 5 mm, 10 mm, and 15 mm; preferably, 5 mm grinding balls, 10 mm grinding balls, and 15 mm grinding balls are blended and used, wherein the mass content of 5 mm grinding balls is not less than 50%.
[0026] Preferably, in the ball milling, the ball-to-material ratio is 2 to 16:1; more preferably 5 to 10:1, and even more preferably 8:1.
[0027] It has been found through experiments that if the ball mill diameter is too large, it will not be conducive to forming a uniform surface coating of SiO containing metal elements. x , which in turn affects the electrochemical properties of the final prepared silicon-oxygen composite material.
[0028] In step (2):
[0029] The carbon coating treatment includes gas phase coating treatment and / or solid phase coating treatment;
[0030] The gas phase carbon source used in the gas phase coating treatment is selected from one or more of methane, ethane, ethylene, acetylene, propyne, acetone and benzene;
[0031] The solid phase carbon source used in the solid phase coating treatment is selected from one or more of asphalt, coal tar, glucose, phenolic resin, citric acid, and polyethylene glycol.
[0032] Carbon coating is a conventional operation method in the art. If gas phase coating is used, it specifically includes:
[0033] In an inert atmosphere, a gaseous carbon source is introduced into a reactor, heated to 650-900° C. to perform vapor deposition of silicon 2 oxide, and then cooled to room temperature.
[0034] The thickness of the carbon layer formed by coating can be controlled by regulating the flow rate of the gas phase carbon source and the temperature and time of the deposition process.
[0035] If solid phase coating is used, it specifically includes:
[0036] Silicon dioxide and a solid carbon source are fully mixed and then heated to 450-900° C. in an inert atmosphere to decompose and carbonize the solid carbon source, and then cooled to room temperature.
[0037] The thickness of the carbon layer formed by coating can be controlled by regulating the amount of solid carbon source and the temperature and time of the deposition process.
[0038] After the above carbon coating treatment, the thickness of the carbon layer formed by the coating is controlled to be 1 to 100 nm; preferably, the thickness of the carbon layer formed by the coating is controlled to be 5 to 30 nm.
[0039] The inert gas described in the present invention is a conventional concept in the art, including nitrogen, argon, helium, helium, etc.
[0040] In step (3):
[0041] In this step, the purpose of adding the acidic solution is to remove the SiO x The metal element layer coated on the surface is removed, thereby forming a porous structure on the carbon layer. Therefore, there is no special requirement for the type of acidic solvent, and it can be selected from the common types in the field. Such as one or more of hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution, phosphoric acid aqueous solution, acetic acid aqueous solution, citric acid aqueous solution, and oxalic acid aqueous solution;
[0042] Preferably, the concentration of the acidic solution is 0.1 to 5.0 M, and the pickling treatment time is 0.5 to 5.0 h.
[0043] The SiO2 having a porous carbon-containing coating layer obtained after the above pickling treatment x The specific surface area of the material is 1 to 30 m 2 / g; preferably 1.8 to 8.7 m 2 / g; more preferably 5.3m 2 / g.
[0044] In step (4):
[0045] The pre-lithiation reagent is selected from one or more of lithium hydride, lithium nitride, lithium borohydride, metallic lithium, lithium amide, alkyl lithium, and lithium carbon compounds;
[0046] The alkyl lithium is selected from one or more of methyl lithium, ethyl lithium, isopropyl lithium, tert-butyl lithium, n-eicosyl lithium, and phenyl lithium;
[0047] The lithium carbon compound is selected from Li2C2, Li4C, Li6C2, Li8C3, Li6C3, Li4C3, Li4C5, LiC6, LiC 12 ,LiC 18 One or more of .
[0048] Through experiments, the preparation process disclosed in the present invention is not only applicable to highly active metallic lithium, lithium hydride, and lithium carbon compounds with low activity, but also to pre-lithiation reagents such as lithium nitride, lithium borohydride, alkyl lithium, and lithium amide with activity between the two. Through experiments, it is found that the preparation process of the present invention can ensure the high reaction efficiency of the above-mentioned pre-lithiation reagents, so that the pre-lithiation reagents are basically free of residue.
[0049] Preferably, the pre-lithiation agent is selected from lithium carbon compounds, more preferably Li4C and / or Li6C2.
[0050] In this step, the SiO2 having a porous carbon-containing coating layer x The mass ratio of the material to the pre-lithiation reagent is 1:0.1-1.0, preferably 1:0.1-0.55.
[0051] When the pre-lithiation agent is selected from lithium carbon compounds, the SiO x The mass ratio of the material to the pre-lithiation reagent is preferably 1:0.1-0.3.
[0052] The calcination treatment is carried out in an inert atmosphere or under vacuum conditions. The calcination temperature and time can be set to ensure that the pre-lithiation reaction is fully carried out. Conventional conditions in the art are used, such as a calcination temperature of 500 to 800° C. and a time of 1 to 8 hours.
[0053] In step (5), the coating is specifically:
[0054] The organic silicon source is mixed with a solvent to obtain an organic silicon source solution, and the pre-lithiated SiO x Mixing evenly with the organic silicon source solution, and drying to remove the organic solvent;
[0055] The organic silicon source is selected from one or more of silane coupling agent, silicone oil, high temperature vulcanized silicone rubber, liquid silicone rubber, and silicone resin;
[0056] The solvent is selected from one or more of ethanol, propanol, isopropanol, methanol, butanol, acetone, ether, ethyl acetate, benzene, toluene, pentane and hexane;
[0057] The concentration of the organic silicon source solution is 1 to 40 wt %, preferably 1 to 10 wt %, and more preferably 1 to 5 wt %.
[0058] The pre-lithiated SiO x The mass ratio of the organic silicon source is 1:0.001 to 0.1; preferably 1:0.005 to 0.05; more preferably 1:0.01 to 0.03.
[0059] The post-processing includes breaking up and / or screening.
[0060] The present invention also discloses a silicon-oxygen composite material prepared according to the above method, comprising a three-layer structure, namely a silicon-based material core, a porous conductive carbon layer and an organic silicon modified layer;
[0061] The silicon-based material core comprises one or more of Si, Li2Si2O5, and Li2SiO3; the median particle size is 1.0 to 10.0 μm;
[0062] The thickness of the porous conductive carbon layer is 2.0 to 100.0 nm;
[0063] The thickness of the organosilicon modified layer is 1.0 to 100.0 nm.
[0064] Preferably, the median particle size of the silicon-based material core is 2.0 to 8.0 μm; more preferably, it is 4.0 to 7.0 μm.
[0065] Preferably, the thickness of the porous conductive carbon layer is 5.0 to 40.0 nm.
[0066] Preferably, the thickness of the organosilicon modified layer is 1.0 to 20.0 nm.
[0067] Preferably, the pH value of the silicon-oxygen composite material prepared in the present invention is 7 to 10; more preferably 7 to 9.8, and even more preferably 8.0 to 9.8.
[0068] The present invention also discloses the application of the silicon-oxygen composite material in a lithium-ion battery. The lithium-ion battery assembled using the silicon-oxygen composite material as the negative electrode material has excellent first coulombic efficiency, first reversible capacity and high cycle stability.
[0069] Compared with the prior art, the present invention has the following beneficial effects:
[0070] The preparation method of the silicon-oxygen composite material disclosed in the present invention adopts the method of coating silicon with metal or metal oxide and then pickling to construct a carbon layer with a porous structure, and obtains SiO2 with a porous carbon coating layer having a suitable specific surface area. x The material is further prepared through a pre-lithiation reaction and a coating of an organic silicon layer to obtain a silicon-oxygen composite material. This preparation method can not only improve the reaction efficiency of the pre-lithiation reagent, significantly reduce the residual amount of the pre-lithiation reagent, but also effectively alleviate the volume expansion of the silicon-oxygen material;
[0071] The silicon-oxygen composite material prepared by the invention has a pH value of 7-10, the prepared slurry has no gas generation phenomenon, and the lithium ion battery assembled with the silicon-oxygen composite material as the negative electrode material has excellent first coulomb efficiency, first reversible capacity and high cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 This is a SEM image of SiO with copper element on its surface prepared in step (1) of Example 1;
[0073] Figure 2 This is a SEM image of the SiO material with a porous carbon-containing coating layer prepared in step (3) of Example 1;
[0074] Figure 3TEM image of the silicon-oxygen composite material prepared in Example 1;
[0075] Figure 4 This is a SEM image of the SiO material with a porous carbon-containing coating layer prepared in step (3) of Example 4;
[0076] Figure 5 This is the SEM image of the SiO material prepared after ball milling in step (1) of Comparative Example 2. DETAILED DESCRIPTION
[0077] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below in conjunction with the embodiments and drawings. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0078] The performance parameters of the intermediate products and final products in the following examples and comparative examples are measured according to the following methods.
[0079] 1. Specific surface area BET and porosity: measured by low temperature nitrogen adsorption method using a specific surface area tester (American Micromeritics TristarⅡ3020).
[0080] 2. Residual amount of pre-lithiation reagent: 90% by weight of deionized water and 10% by weight of silicon-oxygen composite material are thoroughly stirred and mixed evenly. After solid-liquid separation, the amount of residual lithium carbonate and / or lithium hydroxide is titrated separately using acid-base neutralization chemical titration method.
[0081] 3. pH value of silicon-oxygen composite material: 5 g of the prepared silicon-oxygen composite material was thoroughly stirred and mixed with 45 g of deionized water, and solid-liquid separation was performed using a suction filtration device. The pH value of the liquid phase was tested using a potentiometric pH meter, which was recorded as the pH value of the silicon-oxygen composite material.
[0082] 4. Gas production of silicon-oxygen composite materials: Mix the prepared silicon-oxygen composite materials with binder AONE, conductive material SP and dispersant CMC in a mass ratio of 75:10:15:5 to form a slurry. Put part of the slurry into a sealed bottle, cover the bottle with a balloon, and observe the degree of balloon expansion.
[0083] Example 1
[0084] (1) 10.0 kg of SiO (D50 = 6.0 μm, purchased from Yunnan Lichen New Materials Technology Co., Ltd.) and 0.6 kg of metallic copper powder (D50 = 0.5 μm, purchased from Shanghai Sinopharm Reagent Group) were placed in a ball mill, and 2.5 L of anhydrous ethanol was added. Zirconium balls with diameters of 15 mm, 10 mm, and 5 mm were mixed in a mass ratio of 2:3:5, totaling 80 kg. After ball milling for 5 h, the mixture was taken out to obtain SiO with copper on the surface.
[0085] Figure 1 This is a SEM image of SiO2 prepared in step (1) with copper on its surface. From this image, it can be found that the surface of SiO2 is evenly coated with metallic copper powder.
[0086] (2) 10 kg of the SiO2 containing copper on its surface was placed in a CVD rotary furnace, ethylene was introduced as a gaseous carbon source, nitrogen was introduced as a protective gas, and the mixture was deposited at 900° C. for 5 h. After cooling, the SiO2 material containing a carbon coating layer was obtained.
[0087] (3) 10 kg of SiO2 material containing a carbon coating layer was taken and immersed in a 2.0 mol / L hydrochloric acid aqueous solution for washing for 2 h, and solid-liquid separation was performed to obtain a SiO2 material containing a carbon coating layer having pores.
[0088] Figure 2 This is a SEM image of the SiO material with a porous carbon-containing coating layer after the acid washing treatment in step (3). From the image, it can be found that obvious holes appear in the carbon layer coated on the surface of the SiO.
[0089] According to the BET test, the specific surface area of the prepared SiO material with a porous carbon-containing coating layer is 5.3 m 2 / g, and the porosity is 1.5%.
[0090] (4) 4.0 kg of the above-mentioned SiO material with a porous carbon-containing coating layer and 0.62 kg of Li4C were put into a mixer under an argon atmosphere and mixed for 1 hour to obtain a mixed powder material, which was put into an atmosphere furnace and calcined at 730°C for 6 hours under an argon atmosphere, and then cooled to room temperature to obtain pre-lithiated SiO.
[0091] (5) 1.0 kg of the pre-lithiated SiO prepared above was added to 0.83 kg of vinyltrimethylethoxysilane / acetone solution (concentration of 3.0 wt%), and after being fully stirred for 0.5 h, the material was filtered, dried, and then broken up and sieved to obtain a silicon-oxygen composite material.
[0092] Figure 3 This is the TEM image of the silicon-oxygen composite material prepared in this embodiment. By observing the image, it can be found that the prepared silicon-oxygen composite material has a three-layer coating structure. The outermost layer is a coated silicone modified layer with a thickness of about 5nm, which plays a hydrophobic modification role; the middle layer is a conductive carbon layer with a thickness of about 18nm, which enhances the conductivity of the material.
[0093] According to chemical analysis, the residual amount of pre-lithiation reagent Li4C in the final prepared silicon-oxygen composite material was 1200 ppm.
[0094] Example 2
[0095] The preparation process is basically the same as that in Example 1, except that the mass of the metal copper powder added in step (1) is replaced with 0.1 kg.
[0096] According to the test, the specific surface area of the SiO material with a porous carbon-containing coating layer prepared in step (3) of this embodiment is 1.8 m 2 / g, and the porosity is 0.3%.
[0097] According to chemical analysis, the residual amount of pre-lithiation reagent Li4C in the final prepared silicon-oxygen composite material was 2300 ppm.
[0098] Example 3
[0099] The preparation process is basically the same as that in Example 1, except that the mass of the metal copper powder added in step (1) is replaced with 1.0 kg.
[0100] According to the test, the specific surface area of the SiO material with a porous carbon-containing coating layer prepared in step (3) of this embodiment is 8.7 m 2 / g, and the porosity is 3.6%.
[0101] According to chemical analysis, the residual amount of pre-lithiation reagent Li4C in the final prepared silicon-oxygen composite material was 1060 ppm.
[0102] Example 4
[0103] The preparation process is basically the same as that in Example 1, except that the mass of the metal copper powder added in step (1) is replaced with 2.5 kg.
[0104] According to the test, the specific surface area of the SiO material with a porous carbon-containing coating layer prepared in step (3) of this embodiment is 15.4 m 2 / g, and the porosity is 8.2%.
[0105] Figure 4 This is a SEM image of the SiO material with a porous carbon-containing coating layer after the acid pickling treatment in step (3) of this embodiment. From the image, it can be found that the carbon layer coated on the surface of the SiO has obviously collapsed, and the carbon coating layer is incomplete and has obvious defects.
[0106] According to chemical analysis, the residual amount of pre-lithiation reagent Li4C in the final prepared silicon-oxygen composite material was 940 ppm.
[0107] Example 5
[0108] The preparation process is basically the same as that in Example 1, except that the mass of the metal copper powder added in step (1) is replaced with 5.0 kg.
[0109] According to the test, the specific surface area of the SiO material with a porous carbon-containing coating layer prepared in step (3) of this embodiment is 27.4 m 2 / g, and the porosity is 17.4%.
[0110] SEM characterization showed that the carbon layer coated on the surface of the SiO material with pores and carbon coating obtained after acid washing also showed obvious collapse.
[0111] According to chemical analysis, the residual amount of pre-lithiation reagent Li4C in the final prepared silicon-oxygen composite material was 800 ppm.
[0112] Example 6
[0113] The preparation process is basically the same as that in Example 1, except that the total weight of the zirconium balls added in step (1) is replaced by 159 kg, which is obtained by mixing zirconium balls with diameters of 15 mm and 5 mm in a mass ratio of 2:5.
[0114] Example 7
[0115] The preparation process is basically the same as that in Example 1, except that the total weight of the zirconium balls added in step (1) is replaced by 21.2 kg, which is obtained by mixing zirconium balls with diameters of 10 mm and 5 mm in a mass ratio of 2:5.
[0116] Example 8
[0117] The preparation process is basically the same as that in Example 1, except that the metal copper powder added in step (1) is replaced by an equal mass of sodium oxide.
[0118] Example 9
[0119] The preparation process is basically the same as that in Example 1, except that the metal copper powder added in step (1) is replaced by an equal mass of metal magnesium.
[0120] Example 10
[0121] The preparation process is basically the same as that in Example 1, except that the metal copper powder added in step (1) is replaced by an equal mass of aluminum oxide.
[0122] Embodiment 11
[0123] The preparation process is basically the same as that in Example 1, except that the metal copper powder added in step (1) is replaced by an equal mass of metal tin.
[0124] Example 12
[0125] The preparation process is basically the same as that in Example 1, except that the metal copper powder added in step (1) is replaced by an equal mass of metal zinc.
[0126] Embodiment 13
[0127] The preparation process is basically the same as that in Example 1, except that the metal copper powder added in step (1) is replaced by an equal mass of titanium oxide.
[0128] Embodiment 14
[0129] The preparation process is basically the same as that in Example 1, except that the pre-lithiation reagent added in step (4) is replaced by 0.4 kg of Li6C2.
[0130] Embodiment 15
[0131] The preparation process is basically the same as that in Example 1, except that the pre-lithiation reagent added in step (4) is replaced by 1.2 kg of LiC 18
[0132] Example 16
[0133] The preparation process is basically the same as that in Example 1, except that the pre-lithiation reagent added in step (4) is replaced by 0.48 kg of lithium hydride.
[0134] Embodiment 17
[0135] The preparation process is basically the same as that in Example 1, except that the pre-lithiation reagent added in step (4) is replaced by 0.7 kg of lithium nitride.
[0136] Embodiment 18
[0137] The preparation process is basically the same as that in Example 1, except that the pre-lithiation reagent added in step (4) is replaced by 2.18 kg of ethyl lithium.
[0138] Embodiment 19
[0139] The preparation process is basically the same as that in Example 1, except that the pre-lithiation reagent added in step (4) is replaced by 1.39 kg of lithium amide.
[0140] Embodiment 20
[0141] The preparation process is basically the same as that in Example 1, except that the pre-lithiation reagent added in step (4) is replaced by 0.42 kg of metallic lithium.
[0142] Embodiment 21
[0143] The preparation process is basically the same as that in Example 1, except that the SiO in step (1) is replaced by an equal mass of SiO 0.8(D50 = 5.4 μm, purchased from Yunnan Lichen New Materials Technology Co., Ltd.); at the same time, the organic silicon source solution in step (5) was replaced with an equal concentration and mass of γ-aminopropyltriethoxysilane / acetone solution.
[0144] Embodiment 22
[0145] The preparation process is basically the same as that in Example 1, except that the SiO in step (1) is replaced by an equal mass of SiO 1.5 (D50 = 5.7 μm, purchased from Yunnan Lichen New Materials Technology Co., Ltd.); at the same time, the organic silicon source solution in step (5) was replaced with a vinyltrichlorosilane / acetone solution of equal concentration and mass.
[0146] Embodiment 23
[0147] The preparation process is basically the same as that in Example 1, except that step (2) is as follows:
[0148] (2) Take 10 kg of SiO2 containing copper on its surface prepared in step (1) and mix it thoroughly with 0.5 kg of asphalt in a V-type mixer. Put the mixed material into an atmosphere furnace and bake it at 900°C for 5 h in a nitrogen atmosphere. After cooling, take out the SiO2 material containing a carbon coating layer.
[0149] Comparative Example 1
[0150] (1) 10 kg of SiO (D50 = 6.0 μm) was placed in a CVD rotary furnace, ethylene was introduced as a gaseous carbon source, nitrogen was introduced as a protective gas, and deposition was performed at 900° C. for 5 h. After cooling, the SiO material containing a carbon coating layer was obtained.
[0151] (2) 4.0 kg of the SiO material containing the carbon coating layer and 0.62 kg of Li4C were put into a mixer under an argon atmosphere and mixed for 1 hour to obtain a mixed powder material, which was put into an atmosphere furnace and calcined at 730°C for 6 hours under an argon atmosphere, and then cooled to room temperature to obtain pre-lithiated SiO.
[0152] (3) 1.0 kg of the pre-lithiated SiO prepared above was added to 0.83 kg of vinyltrimethylethoxysilane / acetone solution (concentration of 3.0 wt%), and after being fully stirred for 0.5 h, the material was filtered, dried, and then broken up and sieved to obtain a silicon-oxygen composite material.
[0153] Comparative Example 2
[0154] The preparation process is basically the same as that in Example 1, except that the total weight of the zirconium balls added in step (1) is replaced with 10.6 kg, and specifically zirconium balls with a diameter of 20 mm are used.
[0155] Figure 5This is the SEM image of the SiO material after ball milling. From the image, it can be found that only a small amount of copper powder is coated on the SiO surface, and most of the copper powder is agglomerated.
[0156] Comparative Example 3
[0157] Steps (1) to (4) are exactly the same as those in Example 1, and then the pre-lithiated SiO prepared in step (4) is directly filtered, dried, and then broken up and sieved to obtain a silicon-oxygen composite material.
[0158] Comparative Example 4
[0159] Steps (1) to (4) are exactly the same as those in Example 1.
[0160] (5) The pre-lithiated silicon-oxygen material prepared as described above is placed in a chemical vapor deposition furnace, and after argon replacement, methane gas is introduced, and the temperature of the chemical vapor deposition furnace is raised to 700°C and kept warm for 4 hours to perform chemical vapor decomposition deposition. After the deposition is completed, the introduction of methane gas is stopped, and the carbon-coated pre-lithiated silicon-oxygen material is obtained after natural cooling.
[0161] Comparative Example 5
[0162] Steps (1) to (4) are exactly the same as those in Example 1.
[0163] (5) 1.0 kg of the pre-lithiated SiO prepared above was added to 0.83 kg of lauric acid / ethanol solution (concentration of 3.0 wt%), and after being fully stirred for 0.5 h, the material was filtered, dried, and then broken up and sieved to obtain a silicon-oxygen composite material.
[0164] The pH values and gas production of the silicon-oxygen composite materials prepared in the above embodiments and comparative examples are listed in Table 1 below.
[0165] Table 1
[0166]
[0167]
[0168] Performance Testing
[0169] The silicon-oxygen composite materials prepared in the above-mentioned embodiments and comparative examples were assembled into batteries and subjected to electrochemical performance tests. The specific assembly and testing processes are as follows.
[0170] 1. Preparation of liquid lithium-ion batteries
[0171] (1) Preparation of positive electrode
[0172] The positive electrode active material lithium nickel cobalt manganese oxide (NCM811), conductive agent SuperP, carbon nanotubes, binder polyvinylidene fluoride (PVDF) are mixed with N-methylpyrrolidone (NMP) in a mass ratio of 97:1:0.5:1.5 to form a positive electrode slurry (solid content of 70%), coated on the current collector aluminum foil, dried at 70°C, cold pressed at 4MPa at room temperature, and then trimmed, cut, and striped, and the pole ears are welded to make positive electrode sheets.
[0173] (2) Preparation of negative electrode
[0174] Under an inert protective atmosphere, the silicon-oxygen composite material for lithium-ion batteries of the embodiment of the present invention or the comparative material of the comparative example is fully mixed with natural graphite (particle size D50 = 15 μm, purchased from B&T Company) in a ratio of 1:9 to obtain a negative electrode active material, and the negative electrode active material, conductive agent SuperP, adhesive PVDF are mixed with NMP in a mass ratio of 97.5:1.0:1.5 to form a negative electrode slurry (solid content of 50%), which is coated on the current collector copper foil, dried at 100°C, cold pressed at room temperature at 4 MPa, and then trimmed, cut, and stripped, and the pole ears are welded to make a negative electrode sheet.
[0175] (3) Assembly of lithium-ion batteries
[0176] Using PE porous polymer film as a separator, the prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrode sheets, and the bare battery cell is wound; the bare battery cell is placed in an aluminum plastic shell package, and dried at 100°C to a moisture content of less than 100ppm under a relative vacuum pressure of -0.95×105Pa. The electrolyte is injected into the dried bare battery cell, wherein the electrolyte is composed of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (concentration 1.0M), and the battery is packaged, left to stand, formed (0.02C constant current charging for 2h, 0.1C constant current charging for 2h), shaped, and capacity tested (capacity separation) to make a soft-pack lithium-ion battery.
[0177] 2. Testing of lithium-ion batteries
[0178] 2.1 First Coulomb efficiency test:
[0179] The battery prepared above was formed and divided into different capacities using a battery test cabinet. The formation process was to charge at a constant current of 0.05C for 2.0h, and then at a constant current of 0.15C for 2.5h; the division process was to charge at a constant current of 0.33C to 4.2V, and then at a voltage of 4.2V, constant voltage charge to a cutoff current of 0.02C, and discharge at 0.33C to 2.5V; the sum of the above charge capacity and the discharge capacity were recorded as the first charge capacity and the first discharge capacity, and the first reversible specific capacity (mAh / g) was calculated, and the first charge specific capacity, the first discharge specific capacity and the first coulombic efficiency were calculated.
[0180] 2.2 Normal temperature cycle performance test:
[0181] At 25°C, charge the battery to 4.2V at 0.5C constant current and constant voltage, cut off current 0.02C, leave for 5 minutes, then discharge to 2.5V at 1C constant current, leave for 5 minutes. Repeat this cycle, calculate the capacity retention rate of the 500th cycle after 500 cycles of charge / discharge, and the calculation formula is as follows:
[0182] Capacity retention rate at the 500th cycle at room temperature (%)=(discharge capacity at the 500th cycle / discharge capacity at the 1st cycle)×100%.
[0183] Table 2
[0184]
[0185]
Claims
1. A method for preparing a silicon-oxygen composite material, characterized in that: The steps include: (1) SiO x Ball milling with raw materials containing metal elements to obtain SiO x ; The SiO x x is selected from 0.8 to 1.5; The raw material containing metal elements is selected from metals and / or oxides of metal elements, and the metal elements are selected from one or more of the metal elements of the first main group to the fourth main group, and the metal elements of the first sub-group to the seventh sub-group; SiO x The mass ratio of the raw material containing metal elements is 100:1~50; (2) The SiO2 prepared in step (1) with a surface layer containing metal elements x Carbon coating treatment is performed to obtain SiO x Material; (3) The SiO2 containing carbon coating prepared in step (2) x The material was immersed in an acidic solution and then separated after acid washing to obtain a porous carbon-containing coating layer of SiO x Material; (4) The SiO2 having a porous carbon-containing coating layer prepared in step (3) is x The material is mixed with a pre-lithiation agent and calcined to obtain pre-lithiation SiO x ; (5) Using an organic silicon source to treat the pre-lithiated SiO prepared in step (4) x The silicon-oxygen composite material is obtained by coating and then post-processing.
2. The method for preparing the silicon-oxygen composite material according to claim 1, characterized in that: In step (1): The SiO x The median particle size of the raw material containing metal elements is 2.0-8.0 μm, the median particle size of the raw material containing metal elements is 0.01-5.0 μm, and SiO x The median particle size of the raw material is larger than the median particle size of the raw material containing the metal element; The ball-to-material ratio of the ball mill is 2-16:
1.
3. The method for preparing the silicon-oxygen composite material according to claim 1, characterized in that: In step (2): The carbon coating treatment includes gas phase coating treatment and / or solid phase coating treatment; The gas phase carbon source used in the gas phase coating treatment is selected from one or more of methane, ethane, ethylene, acetylene, propyne, acetone and benzene; The solid phase carbon source used in the solid phase coating treatment is selected from one or more of asphalt, coal tar, glucose, phenolic resin, citric acid, and polyethylene glycol.
4. The method for preparing the silicon-oxygen composite material according to claim 1, characterized in that: In step (3): The acidic solution is selected from one or more of hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution, phosphoric acid aqueous solution, acetic acid aqueous solution, citric acid aqueous solution, and oxalic acid aqueous solution; The concentration of the acidic solution is 0.1-5.0M.
5. The method for preparing the silicon-oxygen composite material according to claim 1, characterized in that: In step (4): The pre-lithiation reagent is selected from one or more of lithium hydride, lithium nitride, lithium borohydride, metallic lithium, lithium amide, alkyl lithium, and lithium carbon compounds; The alkyl lithium is selected from one or more of methyl lithium, ethyl lithium, isopropyl lithium, tert-butyl lithium, n-eicosyl lithium, and phenyl lithium; The lithium carbon compound is selected from Li2C2, Li4C, Li6C2, Li8C3, Li6C3, Li4C3, Li4C5, LiC6, LiC 12 ,LiC 18 One or more of; SiO with pores and carbon-containing coating x The mass ratio of the material to the pre-lithiation reagent is 1:0.1~1.0; The calcination treatment is carried out in an inert atmosphere or under vacuum conditions at a temperature of 500-800° C. for a time of 1-8 hours.
6. The method for preparing the silicon-oxygen composite material according to claim 1, characterized in that: In step (5), the coating is specifically: The organic silicon source is mixed with a solvent to obtain an organic silicon source solution, and the pre-lithiated SiO x Mixing evenly with the organic silicon source solution, and drying to remove the organic solvent; The organic silicon source is selected from one or more of silane coupling agent, silicone oil, high temperature vulcanized silicone rubber, liquid silicone rubber, and silicone resin; The solvent is selected from one or more of ethanol, propanol, isopropanol, methanol, butanol, acetone, ether, ethyl acetate, benzene, toluene, pentane and hexane; The concentration of the organic silicon source solution is 1-40wt%; The pre-lithiated SiO x The mass ratio to the organosilicon source is 1:0.001~0.1; The post-processing includes breaking up and / or screening.
7. The method for preparing the silicon-oxygen composite material according to any one of claims 1 to 6, characterized in that: In step (1), SiO x The mass ratio of the raw material containing metal elements is 100:1~10; In step (4), the SiO x The mass ratio of the material to the pre-lithiation reagent is 1:0.1~0.
3.
8. A silicon-oxygen composite material prepared by the method according to any one of claims 1 to 7, characterized in that: It includes a three-layer structure, namely a silicon-based material core, a porous conductive carbon layer and an organic silicon modified layer; The silicon-based material core comprises one or more of Si, Li2Si2O5, and Li2SiO3; the median particle size is 1.0-10.0 μm; The thickness of the porous conductive carbon layer is 2.0-100.0 nm; The thickness of the organosilicon modified layer is 1.0-100.0 nm.
9. Use of the silicon-oxygen composite material according to claim 8 in a lithium-ion battery.
Citation Information
Patent Citations
Pre-lithiated silica composite material as well as preparation method and application thereof
CN114497497A